Strategy for Optimizing Corruption Eradication in Indonesia - Ismawati Septiningsih (Journal of Cross Knowledge, 2024)
The eradication of corruption in Indonesia is still not optimal, as can be seen from the many incomplete judicial processes for corruptors, and the trend of low sentences for corruptors. Apart from that, in terms of recovering assets resulting from corruption, it is also not optimal so that corruption eradication activities are less effective. This research will examine strategies for optimizing the eradication of corruption in Indonesia. This research uses normative legal research methods with a statutory approach. The results of this research are that strategies for optimizing the eradication of corruption can be pursued by imposing the heaviest sanctions for perpetrators of corruption, including criminal sanctions, fines, replacement money, reverse evidence accumulated with money laundering crimes and if possible applying social sanctions